Medical Management of Constipation - Portalatin, Meredith; Winstead, Nathaniel (Clinics in Colon and Rectal Surgery, 2012)
Constipation is a common clinical problem. Initial management of chronic constipation should include lifestyle maneuvers, and increased fiber and fluids. Polyethylene glycol, sodium picosulfate, bisacodyl, prucalopride, lubiprostone, and linaclotide were all more effective than placebo for treating chronic idiopathic constipation. Many commonly used agents lack quality evidence supporting their use.
Keywords: constipation; laxatives; fiber; osmotic agents; polyethylene glycol; 5-ht4 agonists